Computational and experimental assessment of load bearing capacity of glued laminated beams made of beech wood. - Fortuna, Barbara (visokošolska dela, 2022)
Study of the mechanical properties of glued laminated beech beams is presented in this doctoral thesis. The high strength and stiffness properties of beech wood require that special attention be paid to the tensile strength of different finger joint profiles with different adhesives used for longitudinal gluing of beech boards. The results of experimental testing of finger joints in tension have shown that longer and slimmer finger joints are required to increase the load bearing capacity of finger joints. The influence of the type of adhesive used decreases with the length of the finger joints, so that existing structural adhesives are suitable for use with glued laminated beech beams. Fourteen glued laminated beech beams were produced. The beams were then tested and the strength and stiffness properties were measured. In addition to flexural strength and flexural elastic modulus, shear modulus and contact stiffness between layers were measured. Analytical and numerical models for the analysis of glued laminated beech beams were established. The models are based on Reissner’s planar beam theory and take into account the slip between laminations and the influence of finger joints. The analytical solution for Euler-Bernoulli and Timoshenko-Ehrenfest glued laminated beech beams is presented. The numerical model can be used for modelling glued laminated beams with an arbitrary number of laminations and an arbitrary number of finger joints. The model has been validated with the experimental results and the results agree well. Stochastic analysis of glued laminated beech beams is also performed using analytical and numerical model and the results showed a good agreement with the experimental results and that numerical model can simulate the mechanical behaviour of the glued laminated beech beams.
Keywords: adhesive; analitični modeli; analytical model; beech wood; Built Environment; Bukovina; civil engineering; Disertacije; doctoral thesis; finger joints; glued laminated beams; gradbeništvo; Grajeno okolje; lamelirani lepljeni nosilci; lepilo; natezni testi; numerical model; numerični modeli; Spoji; tension testing; zobati spoji